A Developmental Model of Clergy Engagement With Suicide: A Qualitative Study. (September 2019) - Mason, Karen; Geist, Monica; Clark, Mollie
Clergy have a key role in suicide prevention but report being undertrained, perhaps because a model that captures the competencies needed to engage suicide in faith communities and how these skills develop has not previously been available. Using grounded theory, this study addressed this gap by generating a developmental rubric based on interviews with 19 Protestant clergy, which were analyzed using a constant comparative method and were checked by interviewees operating at the highest level of development. The final 10 dimensions described over four developmental stages are (a) knowing role as clergy, (b) listening, (c) confidence, (d) risk assessment, (e) referral, (f) self-care, (g) community building, (h) postvention: ministering to survivors, (i) conducting memorial services or memorial ceremonies, and (j) clergy guilt. Results are based on clergy's intuitive categories and provide a usable rubric for developing suicide prevention training for clergy.